Pengaruh Pemberian Air Kelapa Muda Terhadap Kadar Ureum Pada Tikus Galur Wistar Yang Terpapar Plumbum (Pb) - Siti Thomas Zulaikhah; Joko Wahyu Wibowo (FORIKES, 2020)
Introduction: Plumbum (Pb) is the main air pollutant in urban areas, is one of the heavy metals contained in motor vehicle fuel. Pb is a heavy metal that will trigger the formation of Reactive Oxygen Species (ROS), can reduce the activity of antioxidant enzymes and cause oxidative stress in the kidneys. Tender coconut water contains compounds that are as antioxidants that can protect the effects of free radicals caused by Pb. This study aims to prove the effect of tender coconut water on ureum levels in wistar strain rats exposed to plumbum (Pb). Method: experimental research with posttest only control group design. The independent variable was administration of tender coconut water, while the dependent variable was ureum levels. The study population was wistar strain male rats that were kept in the Penelitian Antar Universitas (PAU) Gajah Mada University, Yogyakarta. The eighteen male wistar strain rats used in this study were divided into 3 random groups, namely the K1 (control); K2 (Pb of 10 mg / day given inhalation); K3 (tender coconut water 8mL /200grBW). Urea levels were analyzed by the Kruskal Walls test, because the data distribution was not normal. Results: The mean ureum levels K1: 11,13 ± 0,51 mg / dL; K2: 52.85 ± 1.97 mg/dL; K3: 19.71 ± 1, 25 mg / dL. The mean ureum level in K2 was higher with K1 and K3, but in K3 it decreased when compared to K2 although it was still higher than K1. The analysis test results obtained p: 0,000 (p value